Rancang Bangun Sistem Informasi Akuntansi Pembelian Bahan Baku Pada Martabak Apin Karawang - Dede Nurrahman (Prosiding Seminar Nasional Teknoka, 2020)
The development of technology today is very rapid, computer device is one electronic tool that was created to simplify and accelerate human work. Martabak Apin Karawang is one of the culinary business.The existing system at Martabak Apin Karawang is only a simple file and notes. The weakness of the system is not efficient, because it takes time during recording, when processing raw material purchases, as well as delays in searching the necessary data. Based on the results of research, data processing done with computerization is much better than the manual way so more effective and efficient. The design method used is to use Unified Modeling Language (UML) as a standardization of modeling language to develop software that is built because of the need for visual modeling to specify, describe, build, and documentation of the software system. While the application development tools using the Java programming language Netbeans version 8.1 and Xampp as database storage. The results of this study obtained a computer-based raw material purchasing system. Information obtained from this system is data items, data suppliers associated with the purchase, and monthly purchase reports. The design of this information system is a good solution to solve the problems that exist on this Martabak Apin Karawang, as well as with a computerized system activities will be done more effectively and efficiently.